On Moral Luck and Nonideal Moral Education. Issue 2 (April 2015) - Chinnery, Ann
Abstract In contrast to the Kantian principle that we are morally accountable only for those actions over which we have control, Bernard Williams, Thomas Nagel, and others have argued that luck plays a significant role in the moral life. Put briefly, moral luck is at play when we are appropriately praised or blamed for our moral actions despite the fact that at least some aspects of what we are being judged for lie beyond our control. In this essay, Ann Chinnery discusses the concept and various types of moral luck, and draws on two news stories from the summer of 2013 (one involving an incident in the United States and the other in the United Kingdom) in order to suggest that a nonideal approach to moral education could go some way toward mitigating the morally limiting effects of "constitutive bad luck."